Pelatihan Penulisan Karangan Bebas Untuk Meningkatkan Kreativitas Siswa Sekolah Dasar - Nurma Yurizah; Wisnu Ady Saputra; Reta Ok aUtari; Chalista Thesa Amanda; Yuliantini Eka Putri S.T M.T (Universitas Merdeka Surabaya, 2025)
Creativity is an important element in the learning process, especially at the elementary school level. One way to foster student creativity is through writing skills, particularly writing free-form essays. This article discusses the implementation of free-form essay writing training as a means to improve the creativity of class AVI. Istudentsat SDN 70 OKU, Rantau Kumpai Village. The activity was carried out using a qualitative descriptive method through a participatory approach inthe form of in-classtraining. Data were obtained from observations, interviews, and documentation during the activity. The results show that this training was able to increase students' enthusiasm, self-expression, and originality in writing in class A VI.I SDN 70 OKU. This training also opened up imaginative and emotional space for students in developing story ideas. Recommendations from this activity are the need to integrate writing training into the daily curriculum and support from teachers and parents so that students can continue to express themselves freely and creatively.